Super-high-resolution aerial imagery, digital surface models and 3D point clouds of Meade Fire Scar, Alaska - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
As part of the ThawTrend-Air airborne campaign led by the Alfred Wegener Institute in 2019, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates two data subsets of the Imuruk volcanic field on the northern Seward Peninsula, Alaska, covering approximately 50 km². All images were collected on 10 July 2021.
Keywords: Airborne Data; Alaska; Arctic Landscape Dynamics; Digital Surface Model; Fire Scar; Ice-wedge Polygons; MACS; Orthoimagery; Permafrost; point clouds; Structure-from-Motion